MODELING AND ANALYSIS OF THE STRUCTURE OF THE MITRA SMART CITY PALOPO GENERAL HOSPITAL BUILDING (RSU) BASED ON SAP 2000 - Kastono; Murshal Manaf; Muh.Mulawarman; Gunawan Tari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The modeling and analysis of building structures in this research aims to provide information about modeling techniques and structural analysis of multi-storey buildings that function as hospitals. Buildings standing with medium soil conditions (stiff soil profile) in Palopo City are included in the moderate earthquake area. Structural modeling and analysis was made using the SAP2000 program to obtain the magnitude of the loads acting on the building structure. The building dimensions are determined based on the condition of the columns, beams and plates based on the provisions of SNI 2847:2013. The results of the structural analysis show that the B80 beam element and C30 column element have a load case deviation of 12-16 mm and a load combination of 32-36 mm. The maximum deviation in terms of each floor is based on the earthquake load referring to SNI 1726:2012. The results of this research have been adapted to applicable regulations to produce a safe and comfortable building as a city hospital.